(3GdMOGFb GdfGVQI aj CMcGe GdYJQI GdWGgQIs - (3GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje GdOQGRj, J (B1186(3g` (B1772(3es
(3ChdgG (B:s
(3ChdgG(B: (3GYde Gfg bO GSJaGVJ GdGYJHGQ HGdMK Ydi WdH GdQRb hGdcSH (B.. (3Ydi GdELeGd aj GdWdH hGdGbJVGA Ydi GdLOd hYdi gPG cGf LeGI abGd CUMGH GdCeIs
(3BNQgG (B:s
(3BNQgG(B: (3hbjd HGdKGfj dCfg de jKHJ EdG HEKHGJg adG jQJaY EdG HQaYg hdCfg jMJGL Edi fXQ hGLJgGO cMLQ GdSajg hbO JbOe JMbjb GdcdGe aj Pdc hHjGf bhI Gdbhd GdKGfj GdChd(B. (3Edi gfG BNQ GdcdGe aj gPG GdeLdOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 215s
(3GdPQjYI, L (B6: 208s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis